PENGELOLAAN RISIKO BENCANA PADA PERISTIWA GEMPA BUMI DAN TSUNAMI PALU DALAM PERSPEKTIF KEBIJAKAN PUBLIK DAN TATA KELOLA PEMERINTAHAN DAERAH - Dwi Nurfaisal, Muhammad; Syarkawi, Syarkawi; Windra, Pirma (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Palu City experienced a complex environmental disaster in 2018 involving an earthquake, tsunami, and large-scale liquefaction, which exposed structural weaknesses in local disaster governance. This study examines environmental disaster risk management in Palu from a public policy and local governance perspective. Using a qualitative descriptive method based on policy analysis and literature review, this research evaluates the consistency between Law Number 24 of 2007 on Disaster Management and its implementation at the local level. The findings reveal that disaster risk management policies have been formally adopted; however, their implementation remains fragmented due to limited institutional capacity, weak spatial governance, and insufficient community-based risk reduction. Strengthening policy coherence, improving intergovernmental coordination, and integrating environmental risk considerations into regional development planning are essential for enhancing local disaster resilience.Keywords: disaster risk management, public policy, local governance, Palu disaster.